Essays on asset pricing with financial frictions - Thomas Kjær Poulsen (Copenhagen Business School (CBS), 2019)
The first essay presents new empirical findings which are inconsistent with prominent theories on the investment premium. The investment premium is the positive stock return difierential between firms with low and high asset growth. Asset growth is the annual percentage change in total assets and is typically interpreted as the firm's investments. The investment premium is an integral part of recent factor models which are fundamental tools for both finance academics and practitioners. In the essay I present three new empirical findings. First, I show that firms with low asset growth on average have higher financial leverage. To the extent that firms with higher leverage have higher returns, cross-sectional difierences in leverage account for part of the investment premium. Second, I document that there is no investment premium among zero-leverage firms. Third, I nd that the investment premium increases with firms' refinancing intensities which are the ratio of short-term debt to total debt. These findings re ect firms' financing decisions and are inconsistent with prominent theories using firms' investment decisions to explain the investment premium.
hdl:10398/9734
Keywords: 650; Kapitalmarkttheorie; Kapitalstruktur; Refinanzierung; Unternehmensanleihe; Rendite; Schuldenmanagement; Geld-Brief-Spanne; Finanzmarktökonometrie